Prevalence of non classical congenital adrenal hyperplasia due to 21-hydroxylase deficiency in Greek women with acne: a hospital-based cross-sectional study. - Trakakis, E.; Papadavid, E; Dalamaga, M; Koumaki, D; Stavrianeas, N; Rigopoulos, D; Creatsas, G.; Kassanos, D. (J Eur Acad Dermatol Venereol, 2013)
AIM: To determine the prevalence and frequency of non classical congenital adrenal hyperplasia (NC-CAH) due to 21-OHD at the time of clinical presentation and at the peripubertal period in a substantial sample of Greek women with acne and to investigate the correlation of serum T, 17-OHP and DHEA-S with acne appearance at the time of clinical presentation. METHODS: One hundred and twenty-three unselected women with hyperandrogenemic symptoms were examined. After the ACTH stimulation test, 6 (4.9%) women were diagnosed with NC-CAH due to 21-OHD. RESULTS: There was not any statistical significant difference in the frequency of peripubertal acne between NC-CAH group of patients (6.4%) and patients with hyperandrogenemia of other aetiology (93%), mainly ovarian (P = 0.41). However, there was a statistical significant difference in the prevalence of acne at the time of clinical examination between the two groups (P = 0.04). Acne was present in 83.3% of women with NC-CAH vs. 41.02% of women in the hyperandrogenic group without NC-CAH. A statistically significant decrease of acne from the peripubertal time to the time of clinical examination in the group of women with hyperandrogenemia of other aetiology (-21.37%) was observed compared to women with NC-CAH (P < 0.001). CONCLUSION: We have shown that acne persists from peripubertal period to adult life in NC-CAH women whereas it tends to diminish in women with hyperandrogenemia of other aetiology. Acne is a prominent finding in women with NC-CAH. Serum concentrations of 17-OHP after ACTH stimulation (17-OHP6O ) should be investigated in women with persistent acne in adult life.
Keywords: Acne Vulgaris; Adolescent; Adrenal Hyperplasia, Congenital; Adult; Cross-Sectional Studies; Female; Greece; Hospitals; Humans; Prevalence; Young Adult